Μοντέλο λήψης αποφάσεων αποτελεσματικής τιμολόγησης απομάστευσης ατμού από μονάδα ηλεκτροπαραγωγής - Μουρελάτος Αλέξανδρος; Ρεκλίτης Π.; Οικονόμου Βικτωρία Πέκκα (SPOUDAI Journal of Economics and Business, 2007)
The paper analyzes the case of extracting steam by a electricity generation unit in order to sale it to a district heating company. The methodology that has been followed to determine the selling price of thermal energy is based on the estimate of marginal cost of substitution of lignite generation of electricity by other technologies. The marginal cost of substitution results from the examination of two alternative scenarios for the operation and growth of electrical generation system both without and with steam extraction from a specific lignite fired generation unit. The analysis showed that the marginal cost of substitution due to steam extraction is 6.98 Euro/MWhth in real 2002 prices. By using this cost an effective selling tariff has been designed. JEL Classifications: Q49, L52